Penerapan Model Pembelajaran Discovery Learning untuk Meningkatkan Kemampuan Menganalisis Teks Anekdot Siswa Kelas X SMK Negeri 3 Pekanbaru - Mukhlis, Muhammad; Asnidar, Asnidar; Winarni, Ari (Jurnal Kependidikan Profesi, 2024)
This research aims to determine whether the application of the Discovery Learning Model can improve students' ability to structure anecdotal texts in Class X Indonesian Language Learning at SMK Negeri 3 Pekanbaru. The Discovery Learning model is a learning method where students gain new knowledge that they did not previously know and not through knowledge providers, but rather students discover themselves. Data management in learning is carried out at school after the data is collected, and then analyzed quantitatively and qualitatively. For quantitative analysis, quantitative analysis is used, namely the average value obtained from the test results of each cycle which aims to determine the level of mastery of the material through definitions (1) there was an increase in students' Indonesian language learning outcomes from each cycle, namely 98%. from cycle I grew to 99 percent from cycle I. (2) there was an increase in the percentage of students' attendance, attention, interest, activeness and enthusiasm for learning in the learning process (3) cooperative learning, apart from being able to improve results, can also improve the quality of collaboration between students, and can inspire confidence to solve existing problems